2001
DOI: 10.1054/bjoc.2001.1788
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 resistant mitochondrial toxicity mediated by the isoquinoline carboxamide PK11195 involves de novo generation of reactive oxygen species

Abstract: SummaryResistance to apoptosis is a major obstacle preventing effective therapy for malignancy. Mitochondria localized anti-death proteins of the Bcl-2 family play a central role in inhibiting apoptosis and therefore present valid targets for novel therapy. The peripheral benzodiazepine receptor (PBR) shares a close physical association with the permeability transition pore complex (PTPC), a pivotal regulator of cell death located at mitochondrial contact sites. In this study we investigated the cytotoxicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 40 publications
(39 reference statements)
2
29
0
2
Order By: Relevance
“…Studies using the TAT-STPH-STP peptide on the MDA-MB-231 aggressive human breast cancer cell line showed that the peptide failed to block the inhibitory effect of micromolar concentrations of Ro5-4864 on cell proliferation (data not shown). These results suggest that either this function of micromolar concentrations of highnanomolar-affinity PBR drug ligands is not related to PBR, as previously suggested by Zisterer et al (1998) andFennell et al (2001), or the concentration of the antagonist needed to block the effect of micromolar concentrations of Ro5-4864 is too high to be reached with the culture conditions used.…”
Section: Discussionsupporting
confidence: 55%
“…Studies using the TAT-STPH-STP peptide on the MDA-MB-231 aggressive human breast cancer cell line showed that the peptide failed to block the inhibitory effect of micromolar concentrations of Ro5-4864 on cell proliferation (data not shown). These results suggest that either this function of micromolar concentrations of highnanomolar-affinity PBR drug ligands is not related to PBR, as previously suggested by Zisterer et al (1998) andFennell et al (2001), or the concentration of the antagonist needed to block the effect of micromolar concentrations of Ro5-4864 is too high to be reached with the culture conditions used.…”
Section: Discussionsupporting
confidence: 55%
“…PK11195 has been reported to generate a reversal action on the chemoresistance in cancer cells, independent of the direct activation of PBR. [25][26][27] In this study, PK11195, a putative chemosensitizer, showed further enhancement of their anticancer effects.…”
Section: Discussionmentioning
confidence: 67%
“…This toxicity has been exploited as an effective strategy for treatment of various cancers (14,16,17). Several agents have been used to generate ROS, inside or around cancerous tissues, including D-amino acid oxidase, glucose oxidase, xanthine oxidase, arsenic trioxide, hydrogen peroxide, PK11195, 4-HPR, and dithiophene (18,19).…”
mentioning
confidence: 99%